Explosive synthesis: novel intrinsically safe method and application with micro-channel reactor. (March 2020) - Weifei, Yu; Zhiyong, Wei; Ruijuan, Xu; Mei, Feng; Sen, Li; Guangcheng, Yang
Abstract: Novel Micro-channel method was introduced into explosive synthesis process. The method was discussed hereby with its intrinsic safety including marvelous inner-structure, high heat-transfer efficiency, and high mass-transfer efficiency compared to traditional kettle-based method. Micro-channel reactor for explosive synthesis was established with high precision control, the temperature difference of oil flow between import and export of micro-channel reactors was measured to be no more than 3°C, and the flux fluctuation of reactant flow were measured to be no more than 0.1ml/min. Micro-channel reactor was experimented with TATB explosive synthesis process. Nitration reaction showed no residue of raw material PG and 91.62% HPLC area of target material TNPG, alkoxylation reaction showed no residue of raw material TNPG and 98.01% HPLC area of target material TETNB, amination reaction showed 5.28% HPLC area of raw material and output of target material TATB. It was concluded to be verifiable including micro-channel method, the apparatus, and application in TATB synthesis process